Investigating Issues and Challenges in Utilising WAQF Property - Abd Mutalib, Hasyeilla; Maamor, Selamah (International Journal of Engineering and Technology, 2018)
Waqf property which is a proper, efficient, well managed and organized will give a positive impact to the community especially on socio-economic aspect. Besides, it will also portray the optimum utilisation of the waqf property by the mutawalli in upholding their responsibility. In Malaysian scenario, waqf property is managed and administered by the State Islamic Religious Council (SIRC) who is acting as a sole trustee at the state level. Currently, there are 14 SIRCs who play their role in managing and administering the waqf property. Even though each SIRC plays its role, there are still unutilised waqf property due to several issues and challenges. Therefore, the purpose of this paper is to reveal the issues and challenges faced that lead to the unutilised of waqf property. A qualitative method is employed in this study using library search as well as semi structured interview on the selected SIRC in the Northern Region of Malaysia as a case study. The study revealed that there are four main issues and challenges that contribute to the unutilised of the property such as non-strategic of waqf property location, lack of fundraise, building orientation which is not suitable, and lack of infrastructure and facilities. The findings of this study are hoped to contribute towards better utilisation of waqf property planning for the benefits of ummah social-economy. Â Â